WORLD FINANCIAL SYSTEM: MAIN TENDENCIES AND INNOVATIVE DIRECTIONS OF DEVELOPMENT - Jasurbek Ataniyazov (European Science Publishing, 2025)
The article describes the main trends in the development of the global financial system, considers the factors influencing the stability of the global financial system and its characteristic changes, describes the mechanism for the development of the global financial system, and also provides innovative directions for the development of the global financial system. In particular, on the basis of research, relevant scientific conclusions have been formed through the study of priority areas for reforming the global financial system, issues of reforming global institutions in order to effectively influence the processes of ensuring the stable development of the global financial system in modern conditions.
Keywords: International financial system, innovation, globalization, digital money, Fintech, integration, inflation.